Решите уравнение: 1.  (4x + 5)^2 + (3 - 2x)(8x + 1) = 7

2.   x(x+2)(6-x) = 14 -x(x-2)

  • (4x + 5)^2 + (3 - 2x)(8x + 1) = 7
    16х
    ²+40х+25+24х+3-16х²-2х=7
    62х=-21
    х=-21/62

       x(x+2)(6-x) = 14 -x(x-2)
    х(6х-х²+12-2х)=14-х²+2х
    6х²-х³+12х-2х²-14+х²-2х=0
    -х³+5х²+10х-14=0

    Q  =  (a² - 3b)/9  =  ((-5)² - 3 × (-10))/9  =  6.11111
    R  = ( 2a³ - 9ab + 27c)/54  = ( 2 × (-5)³ - 9 × (-5) × (-10) + 27 × 14)/54  =  -5.96296
    S = Q3 - R2 = 192.66667

    Т.к. S > 0 => уравнение имеет 3 действительных корня:

    x1 = -2.243
    x2 = 6.243
    ;x3 = 1